ADSC Therapy in Neurodegenerative Disorders. Issue 4 (May 2014) - Chan, Tzu-Min; Chen, Julia Yi-Ru; Ho, Li-Ing; Lin, Hui-Ping; Hsueh, Kuo-Wei; Liu, Demeral David; Chen, Yi-Hung; Hsieh, An-Cheng; Tsai, Nu-Man; Hueng, Dueng-Yuan; Tsai, Sheng-Tzeng; Chou, Pei-Wen; et al.
Neurodegenerative disorders, chronic diseases that can severely affect the patient's daily life, include amyotrophic lateral sclerosis, Parkinson's, Alzheimer's, and Huntington's diseases. However, these diseases all have the common characteristic that they are due to degenerative irreversibility, and thus no efficient drugs or therapy methods can mitigate symptoms completely. Stem cell therapy, such as adipose tissue-derived stem cells (ADSCs), is a promising treatment for incurable disorders. In this review, we summarized the previous studies using ADSCs to treat neurodegenerative disorders, as well as their therapeutic mechanisms. We also suggested possible expectations for future human clinical trials involving minimized intracerebroventricular combined with intravenous administration, using different cell lineages to finish complementary therapy as well as change the extracellular matrix to create a homing niche. Depending on successful experiments in relevant neurodegenerative disorders models, this could form the theoretical basis for future human clinical trials.